Prosthodontic rehabilitation using balancing ramp-guided flexible prosthesis in a squamous cell carcinoma patient treated with hemimandibulectomy - Manu Rathee; Prachi Jain; Akanksha Gopal Shetye; Maqbul Alam (Wolters Kluwer Medknow Publications, 2022)
Loss of any anatomical structure leads to functional insufficiency and psychological trauma. Malignant neoplasms of mandible are often surgically treated by hemimandibulectomy which greatly affects the function postoperatively. The amount of dysfunction depends upon the size of resected segment, effect on tongue, number of remaining teeth, and the extent of loss of sensory and motor innervations. This clinical report describes the prosthodontic management of a squamous cell carcinoma patient treated with hemimandibulectomy and rehabilitated using balancing ramp-guided flexible prosthesis to accommodate mandibular deviation and limited mouth opening.